Design Powered by Data: Getting Started with UX Web Analytics. - Arabadzhiev, Lachezar (linkedin.com, 2022)
Learn how you can supercharge your design by using data analysis with expert Lachezar Arabadzhiev, focusing on the core methodologies that are used today.